Implementation of lean principles for performance improvement: Use of VSM+WID for waste identification - Dinis-Carvalho, José (2018)
This article demonstrates the implementation of lean principles for performance improvement in a manufacturing firm. Value stream mapping and waste identification diagrams (VSM+WID) are integrated to assess the level of currently existing waste and the overall current status of the manufacturing flow. The VSM+WID enables an increase in the awareness of relative waste distribution among different processes in the selected case study manufacturing unit. This manuscript demonstrates how to use VSM+WID to understand the current status of the manufacturing flow related challenges such as: overproduction, work-in-process, inefficient use of man-hours (e.g. unbalanced work distribution), etc. It also demonstrates the effectiveness of visualization of the performance gap between the current and future state. The aforementioned type of performance assessment enables effective identification of waste present in a manufacturing flow in order for future improvement initiatives to be taken.